How do you prove #cos^2x(1-sec^2x)=-sin^2x#?

1 Answer
Write your answer here...
Start with a one sentence answer
Then teach the underlying concepts
Don't copy without citing sources
preview
?

Answer

Write a one sentence answer...

Answer:

Explanation

Explain in detail...

Explanation:

I want someone to double check my answer

Describe your changes (optional) 200

1
Bdub Share
Mar 8, 2018

Answer:

See Below

Explanation:

#LHS : cos^2x(1-sec^2x)#

#=cos^2x(-(sec^x-1))#->use the property#1+tan^2x=sec^2x#

#=cos^2x*(-tan^2x)#

#=cancel(cos^2x)*(-sin^2x)/cancel(cos^2x)#

#=-sin^2x#

#=RHS#

Was this helpful? Let the contributor know!
1500
Impact of this question
870 views around the world
You can reuse this answer
Creative Commons License